Analyzing Symbolic Violence Phenomenon in Project Schools - Mithat Korumaz; Tuğba Konal Memiş (Journal of Economy Culture and Society)
The purpose of the study is to determine whether teachers are subjected to symbolic violence by administrators and, if they are, to disclose the practices of symbolic violence, the reasons behind it, and the reactions of teachers in the face of symbolic violence. The study was conducted using a single case-holistic design. The context of this study is a prestigious and well-established project high school located in one of the high-income districts of Istanbul. The participants of the research consisted of 14 project school teachers, all of whom were selected using the criterion sampling method. A semi-structured interview form, observation, and document analysis were employed in the study to collect data. The data were analyzed through thematic analysis. This study highlights three themes that are ‘incidents of symbolic violence’, ‘roots of symbolic violence at project schools’ and ‘reactions to symbolic violence’. The results demonstrate that teachers are exposed to symbolic violence, which is more visible and severe in the vertical hierarchy at school. Symbolic violence practices are exercised not only by administrators but also by the state, colleagues, and parents against teachers. Regarding the reasons for symbolic violence at project schools, administrators with high symbolic capital, pressure groups (parents/media), and pressure on success are prominent. Lastly, the study discloses that teachers mostly succumb when confronted with symbolic violence; however, some of them resist it and even choose to respond or remain unresponsive.